SEX-BASED DIFFERENCES IN AORTIC VALVE CALCIUM AND THE RISK FOR AORTIC STENOSIS - Natalie Marrero, MD (Elsevier, 2024)
Therapeutic Area: Novel Biomarkers Background: Aortic valve calcification (AVC) is the primary underlying process leading to aortic stenosis (AS). In general, women have lower AVC scores compared to men of the same age and the AVC score threshold for severe AS is lower for women. It remains unknown if the long-term risk of AS differs between sexes with similar AVC scores. We aimed to assess the association between AVC and the risk for clinically significant AS stratified by sex using the Multi-Ethnic Study of Atherosclerosis (MESA). Methods: We included 6,812 MESA participants free of cardiovascular disease with AVC measured at Visit 1 using non-contrast cardiac CT. AVC was examined as a continuous (logarithmically transformed, ln (AVC+1)) and categorical variable (0, 1-99, 100-299, ≥300 AU). Incident long-term AS was adjudicated using standard clinical criteria with a median follow up of 16 years. The primary outcome was incident moderate or severe AS. The association between AVC and AS was examined by calculating absolute event rates per 1,000 person-years, and multivariable adjusted Cox Proportional hazards regression. Results: Among those with AVC >0, women were older (71.7 years vs. 69.8 years, p = 0.01) and generally had a higher risk factor burden. There were 65 cases of incident AS for women and 75 for men. There was a similar absolute event rate for incident AS for women and men across the AVC categories. AVC as a continuous variable was strongly associated with an increased risk for incident aortic stenosis for both women (HR 1.91, 95% CI 1.68-2.16) and men (HR 2.13, 95% CI 1.88-2.41). There was no interaction between AVC, as a continuous variable, and sex (p = 0.31) for the association with AS. The adjusted hazard for severe AS was similar across AVC categories for women and men with HR estimates 134.9 (95% CI 45.1-403.9) for women with AVC ≥300 and 132.8 (95% CI 6.2-274.9) for men with AVC ≥300 (Table 1). Conclusions: The association of AVC with the long-term risk for incident AS was similar for women versus men. These findings further emphasize the utility of AVC as a prognostic marker for incident AS.